OS DESAFIOS DA PREVIDÊNCIA SOCIAL NO MERCOSUL: O ACORDO MULTILATERAL DE SEGURIDADE SOCIAL - Carvalho, Guilherme Soares Schulz de (2015)
This paper discusses the welfare protection to workers in the Mercosur since entry into force of the Multilateral Agreement on Social Security (AMSS) in 2005. The overall objective of the research was to identify the criteria for access to and coverage of welfare protection through the AMSS. The specific purpose of research is to analyze the principles of welfare protection to workers and their applicability to the Multilateral Agreement on Mercosur Social Security; identify the number of workers benefiting from the Multilateral Agreement on Social Security of Mercosur from its entry into force and; identify the coverage of welfare protection provided for in AMSS. The research is exploratory and descriptive. The data collection was carried out through bibliographic, documentary and interview research, and the results were organized and presented in three chapters, which starts of the historical struggle for welfare protection to see how this develops regionally in Mercosur and what the main advances and perspectives of this protection in the block. This research aimed to also contribute to the critical analysis of the welfare protection at the regional level and the movement of workers in Mercosur, and concludes that although there is considerable number of circulating workers, a large part still needs protection, especially due to the informality in the labor market. It was also found the need to think of an enlarged citizenship in Mercosur, which in fact universalize access and coverage to this type of social protection.